Alginate oligosaccharides trigger multiple defense responses in tobacco and induce resistance to Phytophthora infestans - Peng, Chune; Xu, Wei; Wang, Xipan; Meng, Fanxiao; Zhao, Yumeng; Wang, Qingbin; Wang, Xinkun; Lodi, Rathna Silviya; Dong, Xiaodan; Zhu, Changxiang; Peng, Lizeng (Frontiers in Plant Science, 2025)
Alginate oligosaccharides (AOSs), important plant immunity inducers, are widely used in agriculture because of their important role in the biological control of crop diseases. However, the mechanism by which AOSs induce plant resistance to pathogens is not clear. Here, we report AOS with a degree of polymerization of 2–5, which was obtained by a newly reported enzyme Aly2. AOS treatment exhibited high activity in enhancing resistance to Phytophthora infestans (P. infestans). AOS significantly induced reactive oxygen species (ROS) accumulation, calcium influx, stomata closure, and callose deposition. The salicylic acid (SA) synthesis-related gene and the defense-related genes were upregulated after AOS treatment. A transcriptome file generated from AOS-treated seedlings verified the SA pathway and suggested the presence of chitin elicitor receptor kinase (CERK). The subsequent results showed that AtCERK1 binds AOS tightly, suggesting that AtCERK1 is responsible for AOS recognition. This study laid a theoretical foundation for the broad application of AOS.